THERAPEUTIC IMPORTANCE OF ARJUNA (TERMINALIA ARJUNA W. & A.) IN AYURVEDA – A CLASSICAL REVIEW - Mehta Mehul; Doshi Krunal; Shukla .V.J. (International Journal of Applied Ayurved Research, 2017)
Ayurveda delineates the use of Arjuna (Terminalia Arjuna W. & A., Combretaceae) for the management of different disease conditions in classical texts. In this article, an attempt has been made to compile as critically and its information related to Arjuna from samhitas, samgraha granthas, nighantus and other published texts. It is observed that 125 different classical formulations contain of Arjuna as an ingredient, which are effective in more than 20 disease conditions. The indications include hridyaroga (heart diseases), vrana (wound), agnimandya (loss of appetite), jwara (fever), shotha (inflammation), kushtha (skin disease), arsha (piles) etc. Different parts of Arjuna are used in about 11 dosage forms; such as swarasa (juice), kwath (decoction), lepa (paste), avaleha (semi-solid preparations), taila (oil), rasa (mineral preparation), rasakriya (water extract), vati (pills), ghruta (fat soluble preparations) and churna .